An Analysis of Seven Characters Played by Noomi Rapace in the “What Happened to Monday” Film - Kadnawi; Anisatun Sa'diyah (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2021)
Literature is a type of writing that uses language in a special way and can be enjoyed by readers or listeners. There are many types of literary works that can be researched, but this study will only focus on one type of literary work, namely film. Character is an important element in literary works, especially in the world of film. Characters give the important roles to make the story in a film more alive. Studying literature through films will help us learn the characterizations in the story and can learn about the personality, culture and habits of the characters who play in the film. The method of this study is descriptive analytical method. Data and data sources are from the scenes and dialogues in the ―What happened to Monday‖ film which are collected by using documenting technique. The data for the research is all sentences in dialogues and shown in all the scenes of the film which are related to the characters’ characterization and moral messages. The conclusion of this research states that The characterizations of the character that are played by Noomi Rapace are Monday, Tuesday, Wednesday, Thursday, Friday, Saturday, and Sunday who have different characters, and there are two categories of moral messages that the researcher had taken from this film, the relations with oneself and the human relations with other humans in the social sphere..